A [3+2] Cyclization of Siloxyalkynes and Isocyanides for the Synthesis of Oxazoles - Wu, An; Sun, Jianwei (Synlett, 2019)
A mild and efficient [3+2] cyclization of siloxyalkynes for the synthesis of aromatic heterocycles is developed. It is a new addition to the cyclization reactions of these versatile species. In the presence of TBAF as promoter, siloxyalkynes react with electron-withdrawing isocyanides to form a range of oxazole products. In this reaction, siloxyalkynes contribute the C–O unit for the cyclization, which is different from previous typical examples where it is a two-carbon contributor. Mechanistic studies provided insights into the mechanism, which involves a ketene intermediate. Based on the mechanistic insight, an alternative catalytic system was also demonstrated to be effective for the same transformation.
Keywords: oxazoles; siloxyalkynes; isocyanides; cyclization